Nutrient Losses and Related Processes in a Seasonally-operated Septic Bed Soil Under Favourable Conditions - Campbell, Alfred James (My University, 1978)
This study assesses the processes of nutrient loss to groundwater and adjacent soils from a seasonally-operated septic system operating under favourable conditions.
In published studies, highly variable results precluded generalizations about nutrient losses from septic systems. For these reasons, a detailed source-to-sink study of a single septic bed was undertaken to (a) estimate nutrient losses from the bed and (b) identify the intensity and spatial distribution of effluent processes within a septic bed soil.
A research site 40 km northeast of Parry Sound on Whitestone Lake was chosen as typical of cottage waste disposal systems. Sampling surveys using 4 deep soil inspection pits and 137 coring sites in the septic bed soil and nearby field and woodland soils were undertaken during the summers of 1974, 1975 and 1976. Spatial mapping of soil properties, multivariate analysis and modelling of soil solution and ions were used to interpret the measurements. Soil solutes, including nutrients, and environmental soil conditions in the septic bed soil and site area were mapped. Nutrient and soil water fluxes in the septic bed and reference sites were estimated from a mathematical model.
The reference sites are characterized by plant cycling of soil solutes, combined with small vertical leaching losses following rain-fall events. The septic bed soil, when in equilibrium with large effluent input, experiences continuous large vertical and lateral leaching losses. As the septic bed soil begins to receive effluent, leaching accelerates and nutrient fluxes increase, becoming more uniform. The septic bed become anaerobic (oxygen diffusion rate (ODR) < 20 μg cmˉ² minˉ¹) from its centre outward at 30-60 cm depth, and within 7 days, the soil surface and lateral sides of the bed are anaerobic. Precipitation of Ca and PO₄ and lowering of PO₄ and Ca levels in solution occurs after two weeks of operation. A marked drop in ionic levels occurs less than two weeks after effluent input ceases. Plant uptake of nutrients becomes larger than leaching losses as leaching by periodic rainfall cycles becomes apparent.
The distribution of nutrient fluxes and decomposition processes varies with depth and from place to place in the septic bed. For example, large lateral effluent fluxes out of the septic bed are associated with small nitrate fluxes (0.659 x 10ˉ⁵ meq cmˉ³ dˉ¹), and anaerobosis (ODR<18 μg cmˉ² minˉ¹). Conversely, large nitrate fluxes (0.150 x 10ˉ⁵ meq cmˉ³ dˉ¹) are associated with moderate effluent fluxes and aerobic soil (ODR>22 μg cmˉ² minˉ¹). The spatial pattern of effluent fluxes also varies markedly within the septic bed, from small net inflows of groundwater (0.016 cm/d), to large effluent outflows, up to 49 cm/d.
Mathematical modelling indicates losses of NO₃ and PO₄ of 0.234 x 10ˉ⁵ and 0.131 x 10ˉ⁴ meq cmˉ³ dˉ¹, respectively, 10³ and 10² greater than in the reference sites. Increased losses of NH₄, at 0.915 x 10ˉ⁷ meq cmˉ³ dˉ¹, are less (10¹ to 10²), and represent less than 12% of the nitrogen losses from the septic bed. This indicates that serious environmental pollution can occur from a septic system operating under favourable conditions.
Large leaching losses of sodium, up to 0.609 x 10ˉ⁴ meq cmˉ³ dˉ¹, from the septic bed soil C horizon indicate long-term changes in soil fabric are occurring, which will probably accelerate effluent flux losses from the septic bed soil, thereby increasing surface water and groundwater pollution. It is concluded that similar estimates of nutrient fluxes must be gathered from many sites before this environmental pollution source can be accurately estimated or effectively controlled.
Keywords: Geography; Geography